Fiziksel aktiviteye katılım motivasyon etkilerinin farklı değişkenlere göre incelenmesi - Döndü Uğurlu; Rafet Ünver; Hakan Yapıcı; Yusuf Bulut (ROL Spor Bilimleri Dergisi)
The study aims to identify the reasons for a less active lifestyle due to the negative impact of modern technology on human life and to investigate the level of motivation to participate in physical activities. This quantitative study involved 939 adult volunteers. Participants were given a personal information form that included variables such as gender, age, education level, marital status, occupation, and monthly income, as well as the Physical Activity Participation Motivation Scale (PAPMS). Data analysis was performed using SPSS version 22.0 and reliability was determined using Cronbach’s alpha analysis (0.704). The data were normally distributed and parametric tests were performed. The study found no significant differences in motivation to participate in physical activity between genders. However, significant differences were found in variables such as age, marital status, education and monthly income. In particular, people aged 21-30 and singles showed higher motivation. In addition, people with a higher level of education and employees in the public sector showed a higher level of participation in physical activity. These results suggest that different life situations are associated with variations in people’s motivation to be physically active. However, since the comparison was made based on independent variables, it is more appropriate to discuss associations rather than direct effects.